Medbox: The Smart Pillbox - MS, Sibin; Pakalomattom, Elisha G; S, Haripriya; KD, Denisious (International Journal of Computer Sciences and Engineering, 2020)
This era created a change in life style of people and as a result more people are becoming vulnerable to diseases. Completion of medicine course is necessary to evict the disease completely from the body and here our aim is to design a system which can remind and monitor the medication schedule of patients. Medbox is a smart pill box which is an assistive system for patients to schedule their medication timings. It comes along with an android application in which user can customize the each cell in the Medbox. The app provides a provision for alerting the caretaker if the patient forgets to take the pill. The Medbox is designed with 21 cells. Assuming a person is taking medicine 3 times a day. During the medication time, the Medbox alert the user using the red light indicator, buzzer and alarm in the phone. The proper medication details of the patient can be monitored by the caretaker by using the app. There is a separate login portal for patient and caretaker. If the patient goes out without taking the Medbox then, the patients will be notified by an alert message. Medbox and phone is connected via Bluetooth. The Medbox and android application are connected via cloud.